Cu-Ni-Si copper alloy sheet material, conductive components, and heat dissipation components
Patent Information
- Application Number
- JP2025283539
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2025-12-26
- Publication Date
- 2026-10-14
AI Technical Summary
【0013】 本発明によれば、高レベルの強度·導電性のバランスを実現し、かつ良好なプレス打抜き性を維持しながら、曲げ加工性にも優れた、コルソン系銅合金板材を実現することができた。 さらに本発明の前記コルソン系銅合金板材を加工して得られる通電部品、および放熱部品を提供することができる。
Smart Images

Figure 2026167445000006 
Figure 2026167445000007 
Figure 2026167445000001
Abstract
Description
Technical Field
[0001] The present invention relates to a Cu-Ni-Si based copper alloy sheet material with improved press punchability and bending workability and a good balance between strength and electrical conductivity, and to current-carrying components and heat dissipation components using the Cu-Ni-Si based copper alloy sheet material as a material.
Background Art
[0002] Cu-Ni-Si based copper alloys (so-called Corson alloys) and Cu-[Ni,Co]-Si based copper alloys in which part or all of Ni is replaced with Co (hereinafter, these types of alloys are collectively referred to as "Corson-based copper alloys") have a relatively good balance between strength and electrical conductivity among copper alloys, and are useful for current-carrying components such as connectors and lead frames, and heat dissipation components of electronic devices. When processing copper alloy sheet materials into current-carrying components or heat dissipation components, it is common to go through press punching and bending processes. Up to now, various studies have been conducted on methods for improving the press punchability and bending workability of Corson-based copper alloys.
[0003] Patent Document 1 discloses a Corson-based copper alloy sheet material containing Co, which on the rolled surface has a twin boundary density of 40% or more among all grain boundaries, an area ratio of Cube orientation crystal grains of 20% or more, an electrical conductivity of 30%IACS or more, and a 0.2% proof stress of 900MPa or more, and simultaneously has excellent bending workability and stress relaxation resistance, as well as a method for producing the same. However, this document does not disclose a material added with S. Patent Document 2 discloses a Corson-based copper alloy sheet material that has, when crystal orientations are analyzed at the central portion in the sheet thickness direction, an area ratio of Cube orientation {0 0 1}<1 0 0> of 10 to 80%, an area ratio of Brass orientation {1 1 0}<1 1 2> of 20% or less, and an area ratio of Copper orientation {1 1 2}<1 1 1> of 20% or less, and has both high strength and high notch bendability. However, this document does not disclose a material added with S. Patent Document 3 discloses a Corson-type copper alloy sheet material in which the surface of the rolled material has a ratio of 1.0 ≤ I(200) / I0(200) ≤ 5.0, the area ratio of Cube orientation {1 0 0}<0 0 1> in EBSD measurement of the rolled parallel cross section is 2 to 10%, and (average grain size of Cube orientation {1 0 0}<0 0 1> in the rolled parallel cross section) / (average grain size of the rolled parallel cross section) is 0.75 to 1.5, and claims to provide a Corson alloy with excellent bendability. However, the document does not show a material with added sulfur.
[0004] Patent Document 4 discloses a Corson-type copper alloy sheet material containing sulfide, wherein sulfides that contribute to improved machinability are dispersed, the average diameter of the sulfides is 0.1 to 10 μm, the area ratio of the sulfides is 0.1 to 10%, and the tensile strength is 500 MPa or more and the conductivity is 25% IACS or more. Patent Document 5 describes a Corson-type copper alloy sheet material containing sulfur, wherein the DAS (dendritic arm spacing) in the ingot is 37 to 108 μm, the average particle size of sulfides dispersed in the ingot is 5 to 10 μm, and the number density is 100 to 1000 particles / mm². 2 The company aims to provide copper alloy ingots, and copper alloy materials obtained by hot working, cold working, and heat treating these copper alloy ingots, which have a tensile strength of 500 MPa or more, an electrical conductivity of 25% IACS or more, and excellent machinability, without using environmentally harmful substances (Pb, Be). Patent document 6 discloses a technique for improving the strength and press-punching properties of a Corson-type copper alloy by adding sulfur and controlling the number density of Mg-S particles. There is no particular teaching regarding the improvement of bendability. In this document, materials with a small proportion of shear surface area on the cut surface are evaluated as having good press-punching properties. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2011-231393 [Patent Document 2] Japanese Patent Publication No. 2012-188689 [Patent Document 3] Japanese Patent Publication No. 2018-159103 [Patent Document 4] Japanese Patent Publication No. 2011-231394 [Patent Document 5] Japanese Patent Publication No. 2012-046812 [Patent Document 6] Japanese Patent Publication No. 2021-134376 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] Recently, with the miniaturization and narrowing of component pitches, copper alloy sheets are required to have high strength and excellent bendability when manufacturing components such as connectors from copper alloy sheets. Meanwhile, in press forming of components, improving the lifespan of press dies is becoming increasingly important. According to the technologies described in Patent Documents 1, 2, and 3, it has been reported that excellent bendability can be obtained in Corson copper alloys by controlling the microstructure, such as the texture. However, for high-strength Corson copper alloys in particular, further improvement in press punchability (improvement of die life by reducing the proportion of shear surface in the cut surface) is required. On the other hand, according to the technologies described in Patent Documents 4, 5, and 6, in Corson-type copper alloys, it is possible to increase strength and improve press-punchability by adding sulfur to create a microstructure in which sulfides are dispersed in the matrix. However, since the addition of sulfur reduces bendability, it is difficult to process small parts that require rigorous bending from such copper alloy sheets.
[0007] The present invention aims to provide a Corson-type copper alloy sheet material that achieves a high level of balance between strength and conductivity, maintains good press-punching properties, and also exhibits excellent bendability. Furthermore, the invention aims to provide conductive components and heat dissipation components obtained by processing the Corson-type copper alloy sheet material. [Means for solving the problem]
[0008] To achieve the above objectives, the following inventions are disclosed herein.
[0009] [1] A copper alloy plate having a chemical composition by mass% consisting of Ni: 1.0-5.0%, Si: 0.2-1.5%, S: 0.001-0.5%, Mn: 0.001-0.5%, Co: 1.5% or less, with the remainder being Cu and unavoidable impurities, and having a volume fraction of {200} crystal planes determined from the X-ray diffraction pattern of the plate surface of 29% or more. [2] The copper alloy sheet material described in [1] above, wherein the (Ni+Co) / Si mass ratio is 3.0 to 6.0. [3] The copper alloy sheet material described in [1] above, wherein the Ni content is 1.0 to 4.5 mass%. [4] The copper alloy sheet material described in [1] above, wherein the tensile strength in the rolling direction is 700 MPa or more. [5] The copper alloy plate material described in [1] above, wherein the conductivity is 40% IACS or higher. [6] The copper alloy sheet material described in [1] above, wherein in a 90° L-shaped bending test at BW, the ratio MBR / t of the minimum bending radius MBR to the sheet thickness t is 1.0 or less. [7] The copper alloy sheet material described in [1] above, further comprising, by mass%, Ag: 0-0.5%, Al: 0-0.5%, B: 0-0.1%, Cr: 0-0.5%, P: 0-0.5%, Sn: 0-0.5%, Ti: 0-0.5%, Zn: 0-0.5%, and Zr: 0-0.5%, with the total content of these being 0.001-1 by mass%. [8] An electrical component made from a copper alloy plate material as described in any one of [1] to [7] above. [9] A heat dissipation component made of copper alloy plate material as described in any one of [1] to [7] above.
[10] A copper alloy plate having a chemical composition by mass% consisting of Ni: 2.5-5.0%, Si: 0.5-1.5%, S: 0.001-0.5%, Mn: 0.001-0.5%, Co: 1.5% or less, with the remainder being Cu and unavoidable impurities, and having a volume fraction of {200} crystal planes determined from the X-ray diffraction pattern of the plate surface of 30% or more.
[0010] In the present specification, "plate material" means a sheet-shaped metal material. A thin sheet-shaped metal material is sometimes called "foil", and such "foil" is also included in the "plate material" as referred to herein. A long sheet-shaped metal material wound in a coil form is also included in the "plate material". Further, in the present specification, the thickness of the sheet-shaped metal material is referred to as "plate thickness". The term "plate surface" means a surface perpendicular to the plate thickness direction of the plate material. The plate surface is sometimes called "rolled surface". In the present specification, the notation "n1 to n2" indicating a numerical range means "not less than n1 and not more than n2". Here, n1 and n2 are numerical values satisfying n1 < n2.
[0011] In the present specification, "press punching property" is an index evaluated by the area ratio of the "shear surface" occupying the fractured surface (cut edge) when punching is performed by a press die with an appropriate clearance. In order to stabilize quality in the punching process, extending the service life of the die is important. On the fractured surface of the metal plate formed by press punching, a shear surface and a fracture surface are usually formed (see Figure 2). When punching is performed with an appropriate clearance, a material having a smaller ratio of the shear surface is more advantageous for extending the service life of the die. Therefore, in the present specification, it is defined that a material having a smaller ratio of the shear surface occupying the fractured surface when punched under the same conditions has better press punching property.
[0012] The total rolling reduction (%) in a certain rolling step is determined by the following formula (1). Total rolling reduction (%) = 100 × (h0 - h1) / h0 ... (1) h0: Plate thickness (mm) before being subjected to the first rolling pass of the rolling step h1: Plate thickness (mm) when the final rolling pass of the rolling step is completed Effects of the Invention
[0013] According to the present invention, it is possible to realize a Corson-type copper alloy plate material that achieves a high-level balance of strength and electrical conductivity, maintains good press punching property, and also has excellent bending workability. Furthermore, the present invention can provide a current-carrying component and a heat dissipation component obtained by processing the above-mentioned Corson-type copper alloy sheet material of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] [Figure 1] It is a schematic cross-sectional view for explaining a 90° L-shaped bending test method. [Figure 2] It is a view schematically showing the shape of the cut end of a metal sheet after press punching. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION
[0015] [Chemical Composition] Hereinafter, "%" relating to the component composition means "mass %" unless otherwise specified.
[0016] The present invention is directed to a Cu-Ni-Si based copper alloy containing S (sulfur) and Mn (manganese) in addition to Ni (nickel) and Si (silicon). Ni and Si form precipitates mainly composed of Ni₂Si and the like, and contribute to the improvement of strength and electrical conductivity. The Ni content can be set in a range of 1.0 to 5.0% (preferably 2.5 to 5.0%) in consideration of hot workability, and the Si content can be set in a range of 0.2 to 1.5% (preferably 0.5 to 1.5%). Within this range, an appropriate strength level to be described later can be obtained. From the viewpoint of the balance between strength and bending workability, Ni is preferably contained in a range of 1.0 to 4.5%, more preferably contained in a range of 1.0 to 4.0%, and particularly preferably contained in a range of 3.0 to 4.0%.
[0017] Further, regarding the chemical composition of the copper alloy sheet material of the present invention, Co (cobalt) forms a Co₂Si-based compound or a (Ni,Co)₂Si-based compound, and contributes to the improvement of strength and electrical conductivity. The Co content is in a range of 0 to 1.5%, and there are cases where it is preferable not to add Co in relation to raw material cost, application, and the like. The (Ni+Co) / Si mass ratio is preferably in the range of 3.0 to 6.0, and more preferably in the range of 3.5 to 5.0. It is believed that by keeping the ratio within this range, much of the Ni and Co contained in the copper alloy reacts with Si to form intermetallic compounds, making it easier to achieve high strength while suppressing a decrease in electrical conductivity.
[0018] S (sulfur) is an important component element in this invention. Generally, in copper alloys, sulfur is often treated as an impurity from the viewpoint of suppressing deterioration of hot workability and reduction of material properties. In the manufacturing process of copper alloys, sulfur content is usually reduced by methods such as degreasing of raw materials and flotation separation in molten metal.
[0019] However, in this invention, sulfur is intentionally added. This is thought to generate and disperse Mn-S system particles as sulfur-containing phase particles in the material, thereby improving press punching performance. In other words, a predetermined amount of sulfur is included in the copper alloy as a source for generating Mn-S system particles. After various studies, it has been found that controlling the sulfur content in the range of S:0.001 to 0.5% is effective. If the sulfur content is too low, it is thought that the amount of sulfur-containing phase particles generated will be insufficient, and the improvement in press punching performance will not be obtained. It is more preferable that the sulfur content be 0.005% or more, and even more preferable that it be 0.008% or more. If the sulfur content is excessive, the hot workability will worsen, and cracks will easily occur during hot rolling. Also, from the viewpoint of obtaining good bendability, a lower sulfur content is more effective. It is preferable to adjust the sulfur content to be in the range of 0.1% or less, more preferably 0.08% or less, and even more preferably 0.05% or less.
[0020] Manganese (Mn) is an essential component in Cu-Ni-Si copper alloy sheet materials, and it is believed that Mn-S particles are formed from it and sulfur, improving press-punching properties. Mn has a lower free energy for sulfide formation at 500°C than Ni and Si, making it an element that readily forms sulfides. By preferentially bonding this element with S over Ni and Si, the consumption of Ni and Si in the copper alloy for sulfide formation is prevented, and a sufficient amount of Mn-S containing particles is ensured to reduce the proportion of shear surfaces in the cut surface of the metal sheet formed during press stamping.
[0021] After various studies, it is necessary to ensure a Mn content of 0.001% or more. A large amount of Mn content will reduce hot or cold workability. On the other hand, from the viewpoint of conductivity, the Mn content is limited to a range of 0.5% or less, preferably 0.2% or less, more preferably 0.1% or less, and may even be controlled to 0.05% or less.
[0022] As other optional elements, one or more elements within the range of Ag: 0-0.5%, Al: 0-0.5%, B: 0-0.1%, Cr: 0-0.5%, P: 0-0.5%, Sn: 0-0.5%, Ti: 0-0.5%, Zn: 0-0.5%, and Zr: 0-0.5% may be included as needed. The total content of these elements is, for example, 0.001-1%.
[0023] Considering the balance of press-punchability, bendability, strength, and conductivity, as well as economic efficiency and manufacturability, it is preferable that the total content of these optional elements be 0.5% by mass or less.
[0024] The chemical composition of the copper alloy sheet material according to the present invention can be specified as "consisting of Ni, Si, S, Mn, Co, any of the above elements (including cases where the total is 0% by mass), the remainder being Cu and unavoidable impurities." It is desirable that the material substantially does not contain elements that form sulfides more readily than Mn (elements whose free energy for sulfide formation at 500°C is lower than that of Mn).
[0025] [Volume fraction of {200} crystal planes] {200} crystal plane ({100} <001> The orientation is generally called the Cube orientation, and because it is easily deformed by sliding, it can be made to have good bendability. The inventors have found that by setting the volume fraction of the {200} crystal plane, determined from the X-ray diffraction pattern, to 29% or more, sufficient bendability can be achieved in the conductive member. The volume fraction of the {200} crystal plane is preferably 30% or more, more preferably 40% or more, and even more preferably 45% or more. The volume fraction is usually 70% or less.
[0026] [Tensile strength] The copper alloy sheet material of the present invention can achieve high strength with a tensile strength of 700 MPa or more in the rolling direction, preferably 850 MPa or more, 860 MPa or more, and even 880 MPa or more. Note that the tensile strength in the rolling direction of copper alloy sheet material is usually 1100 MPa or less.
[0027] Ni and Si increase the strength of copper alloy sheets through the formation of precipitates. Mn and S are also thought to increase the strength of copper alloy sheets through the formation of Mn-S particles. Furthermore, in the copper alloy sheet manufacturing method of the present invention, which will be described later, the amount of precipitate formation can be adjusted by the temperature and time of the aging treatment, and the final strength of the sheet can be adjusted by the total rolling ratio of the finish cold rolling.
[0028] [conductivity] Furthermore, the copper alloy sheet material of the present invention simultaneously achieves an conductivity of 40% IACS or higher. This high level of strength-conductivity balance can meet the needs for thinner and smaller conductive components. The conductivity of Cu-Ni-Si copper alloy sheet material is typically 55% IACS or lower.
[0029] [Bendability] Processing into electrical components and the like often involves bending. Considering the applications of Cu-Ni-Si copper alloy sheets, in order to obtain high reliability when processing into electrical components and heat dissipation components, it is preferable that the material has bendability such that the ratio MBR / t of the minimum bending radius R (MBR) that does not cause cracking when the longitudinal direction of the test piece is perpendicular to the rolling direction (BW) (bending axis is parallel to the rolling direction), with a test piece width of 0.5 mm, and the MBR / t is obtained by determining the minimum bending radius R (MBR) that does not cause cracking when the test piece is bent in a 90° L-shaped bending test, and dividing this by the thickness t of the copper alloy sheet, is 1.0 or less. It is more preferable that the MBR / t in BW is 0.9 or less, and even more preferable that it is 0.8 or less. BW (Bad Way) means that the bending axis is parallel to the rolling direction.
[0030] Generally, there is a trade-off between strength and bendability. However, in the copper alloy sheet material of the present invention, if the Ni content is 3.0 mass% or more, the Si content is 0.7 mass% or more, and the volume fraction of {200} crystal planes is 42% or more, then both bendability with an MBR / t of 1.0 or less and excellent strength with a tensile strength of 850 MPa or more in the rolling direction can be achieved.
[0031] [Manufacturing method] The copper alloy sheet material described above can be manufactured, for example, by the following manufacturing process. Melting and casting → Hot rolling → First intermediate cold rolling (rough rolling) → Intermediate annealing → Final intermediate cold rolling (intermediate rolling) → Solution treatment → Aging treatment → Finish cold rolling → Finish heat treatment (low-temperature annealing) Although not mentioned in the above process, after hot rolling, the surface and sides of the sheet are machined as needed, and after each heat treatment, pickling, polishing, or further degreasing is performed as needed. The following describes each of the above processes.
[0032] [Melting and Casting] Cast slabs can be manufactured using known methods such as mold casting, continuous casting, or semi-continuous casting. To prevent oxidation of silicon and other elements, it is preferable to carry out the process in an inert gas atmosphere or a vacuum melting furnace.
[0033] In the melting of copper alloys, sulfur (S) is generally treated as an impurity, and the raw materials and refining methods are usually controlled to reduce its content as much as possible. In contrast, the present invention requires strict control of the S content so that S within the predetermined content range described above is incorporated into the copper alloy. For example, a pre-prepared Cu-S matrix alloy can be used to add S.
[0034] [Hot rolling] After heating the cast slab to 700-1100°C, a hot-rolled sheet is obtained by hot-rolling the slab to a total rolling ratio of 50% or more. From the viewpoint of promoting the homogenization of the structure, it is more preferable to heat the cast slab to a temperature of 850-1100°C. The heating and holding time of the cast slab is preferably set in the range of 0.5-12 hours. To break up coarse compounds and inclusions and promote the homogenization of the structure, it is more preferable to set the total rolling ratio of the hot-rolling to 70% or more. The upper limit of the total rolling ratio of the hot-rolling can be set according to the capacity of the hot-rolling mill. Usually, it is sufficient to set it in the range of 95% or less.
[0035] [First intermediate cold rolling, intermediate annealing, final intermediate cold rolling] In this invention, a process is employed in which multiple cold rolling steps, interspersed with intermediate annealing, are performed before the solution treatment. The first cold rolling step performed after hot rolling is called the "first intermediate cold rolling (or rough rolling)," and the cold rolling step performed before the solution treatment is called the "final intermediate cold rolling (or intermediate rolling)."
[0036] The first intermediate cold rolling should result in a total rolling ratio of 60% or more. This is to introduce strain that promotes recrystallization during intermediate annealing, and the upper limit of the total rolling ratio can be set according to the capacity of the rolling mill. Typically, it should be set within a range of 99% or less.
[0037] Intermediate annealing, performed between the first intermediate cold rolling and the final intermediate cold rolling, is carried out under conditions of holding at a predetermined temperature for 0.1 to 20 hours, preferably 5 to 18 hours. The predetermined temperature is within the temperature range of {(Ni,Si,S,Mn,(Co))*23+482}±10 (°C). (Ni,Si,S,Mn,(Co)) is the total content of these elements. By performing intermediate annealing in such a specific, limited high-temperature range, the volume fraction of the {200} crystal plane can be increased in the subsequent solution treatment process. However, if the intermediate annealing temperature is too low or the holding time is too short, the strain may not be removed sufficiently, which can lead to problems such as cracking during the subsequent cold rolling. If the temperature is too high or the holding time is too long, the material strength will decrease. Furthermore, when observing the microstructure before and after intermediate annealing, it is preferable that the microstructure after intermediate annealing shows a state where the coarse crystal grains from before intermediate annealing have recrystallized, and the region of fine recrystallized grains has increased.
[0038] It is known that recrystallizing the sheet material structure during intermediate annealing increases the {200} volume fraction after solution treatment. Meanwhile, investigations into the effects of Ni, Si, Co, S, and Mn on the recrystallization temperature confirmed that the relationship between the content of these elements and the recrystallization temperature can be expressed by the above formula. A tendency for the recrystallization temperature to rise with increasing elemental content was observed. This is thought to be due to two factors: solid solution strengthening and grain boundary pinning by precipitates.
[0039] The reason for the solid solution strengthening is that when elements dissolve in the matrix material, distortion occurs in the crystal lattice, hindering dislocation movement, and consequently increasing the recrystallization temperature. The reason for the grain boundary pinning by precipitates is that an increase in fine precipitates enhances the pinning effect that hinders grain boundary movement, resulting in a greater energy requirement for grain boundary movement and thus increasing the recrystallization temperature.
[0040] Furthermore, during intermediate annealing, the material is held at the predetermined temperature, but the heating to that predetermined temperature is carried out over, for example, 1 to 20 hours, preferably 3 to 15 hours.
[0041] The final intermediate cold rolling should ideally result in a total rolling ratio of 70% or more to introduce strain that promotes recrystallization during the subsequent solution treatment. The upper limit of the total rolling ratio can be set according to the capacity of the rolling mill. Typically, it should be set within a range of 99% or less.
[0042] If necessary, one or more intermediate cold rolling and intermediate annealing steps may be inserted between the above-mentioned intermediate annealing and the above-mentioned final intermediate cold rolling. In that case, the same conditions as the above-mentioned intermediate annealing may be used for the inserted intermediate annealing, and the same conditions as the above-mentioned first intermediate cold rolling may be used for the inserted intermediate cold rolling.
[0043] [Solution treatment, aging treatment] Next, a solution treatment is performed at 800-1020°C, preferably 850-1000°C, more preferably 900-1000°C, for 10-600 seconds. Subsequently, an aging treatment is performed at 400-550°C for 1-24 hours. By performing intermediate annealing under the specific heating conditions described above, the volume fraction of {200} crystal planes can be significantly increased by the solution treatment at this stage. Care must be taken in the processes after the solution treatment to avoid reducing the volume fraction of {200} crystal planes.
[0044] [Finishing cold rolling, finishing heat treatment] After aging treatment, finish cold rolling is performed at a total rolling ratio of 10-50%, preferably 40% or less, to obtain the desired sheet thickness. If the rolling ratio is too high, the rolled structure will develop, and there is a risk that the volume fraction of {200} crystal planes will decrease. After finish cold rolling, finish heat treatment is performed for the purpose of reducing residual stress, improving bendability, and improving stress relaxation resistance by reducing voids and dislocations on slip planes. The conditions for the finish heat treatment should be such that the heating conditions do not decrease, with a holding temperature of 140-500°C, preferably 300°C or higher, and a holding time of 5-3600 seconds. The final sheet thickness can be, for example, in the range of 0.02-0.40 mm.
[0045] [Electrical components and heat dissipation components] The Cu-Ni-Si copper alloy sheet material obtained as described above exhibits excellent press-punching properties, good bendability, high strength, and a good balance with electrical conductivity. Furthermore, it can be processed into electrical components such as connectors and heat dissipation components for electronic devices using a processing process that improves mold life and reduces manufacturing costs by avoiding excessive manufacturing load. [Examples]
[0046] Copper alloys with a predetermined chemical composition were melted using a vacuum melting furnace and then cast. The gas phase space in which the molten metal came into contact during casting was maintained under an argon atmosphere. Examples 1 to 11, Comparative Examples 31 to 33, and Comparative Examples 37 to 45 were cast using small test molds, while Comparative Examples 34 to 36 were cast in a continuous casting furnace. A Cu-20.1 mass%S alloy was used for the sulfur addition. Table 1 shows the results of compositional analysis performed on analytical samples taken from the cast slabs using X-ray fluorescence analysis and ICP analysis (inductively coupled plasma emission spectrometry). The values for all examples and comparative examples were similar to those of the raw materials used in casting.
[0047] The obtained cast slabs were heat-treated at the heating temperatures and holding times shown in Tables 2 to 4, then removed from the furnace and subjected to hot rolling with the total rolling ratios shown in Tables 2 to 4 to obtain the plate thicknesses indicated in Tables 2 to 4. After hot rolling, the oxide layer on the surface was removed by mechanical polishing (surface grinding). Subsequently, the first intermediate cold rolling, intermediate annealing, final intermediate cold rolling, solution treatment, aging treatment, finish cold rolling, and finish heat treatment were carried out in the order shown in Tables 2 to 4 under the conditions indicated in Tables 2 to 4. Furthermore, the intermediate annealing temperature (calculated value) in Tables 2 to 4 is the value of {(Ni,Si,S,Mn,(Co))*23+482}, the intermediate annealing temperature (experimental value) is the holding temperature, the heating time for intermediate annealing is the time until the holding temperature is reached, the holding time is the time to hold at the holding temperature, and then furnace cooling was performed. In addition, water cooling was performed after the solution treatment and finish heat treatment, and furnace cooling was performed after the aging treatment. Comparative Examples 34-36 and 45 omitted the first intermediate cold rolling and intermediate annealing. Comparative Example 37 also omitted intermediate annealing. Furthermore, Comparative Example 42 did not proceed to the next step because cracking occurred during hot rolling. Note that the total rolling percentage (%) values for each rolling step listed in the table have been rounded to the nearest whole number.
[0048] In each example, the plate material obtained by the finishing heat treatment was used as the test material for the following investigation. For Examples 1 to 11 and Comparative Examples 31 to 33, an oxide film was formed on the surface, so after the finishing heat treatment, the surface was polished to remove the film and adjust the thickness. The plate thickness of each test material was 0.10 to 0.22 mm as shown in Table 5.
[0049] (conductivity) The conductivity of each test material was measured in accordance with "JCBA T603 2011: Method for Measuring Conductivity Using an Eddy Current Conductivity Meter (Japan Copper Association Working Standards)". Since each test material was thin, multiple pieces were stacked to a thickness of 0.5 mm or more (3 pieces for Examples 1-3, 8, 10 and 11 and Comparative Examples 31-33; 4 pieces for Examples 4-7 and 9 and Comparative Examples 37-41 and 43-45; and 5 pieces for Comparative Examples 34-36) for measurement. Considering the conductivity required for conductive components such as small connectors, a conductivity of 40% IACS or higher was judged as acceptable.
[0050] (Tensile strength) Tensile test specimens (JIS No. 5) were taken from each test material in the rolling direction, and tensile tests were conducted in accordance with JIS Z2241 to measure the tensile strength. From the perspective of ensuring bendability and high reliability in electrically conductive components such as connectors, specimens with a tensile strength of 700 MPa or higher in the rolling direction were judged to be acceptable.
[0051] (Bendability) The bendability of each test material was evaluated by a 90° L-shaped bending test. With the bending axis parallel to the rolling direction and the width of the test piece 0.5 mm, the test piece was fixed between the die and the presser as shown in Figure 1, and then the punch was lowered to bend the test piece by 90°. The state of the punch and test piece in the bent state is shown by the dotted line in Figure 1. The distance between the punch and the die is the thickness of the test piece plus a clearance of 0.01 mm. After that, the punch was returned to its original position and the test piece was removed. For this test piece, the minimum bending radius R (MBR) at which no crack occurred on the convex bent surface was determined, and the ratio of the minimum bending radius MBR to the thickness t of the test piece MBR / t was obtained by dividing it by the thickness t of the copper alloy sheet material.
[0052] The presence or absence of cracks on the bent surface was determined according to JCBA T307:2007. For samples judged as "large wrinkles" in the visual inspection of the bent surface, a sample was prepared by cutting perpendicular to the bending axis at the deepest wrinkled part, and the polished cross-section was observed with an optical microscope to check whether cracks propagating into the thickness of the plate had occurred. If no such cracks were found, it was judged as "no cracks observed." Considering the intended use of the material of the present invention, samples with an MBR / t of 1.0 or less in this test were judged as acceptable. In addition, for all examples and comparative examples except Comparative Example 42, the bendability evaluation test was performed when R / t was 1.0.
[0053] (Press punching capability) For the test material, a test was conducted in which 5mm x 5mm square test pieces were punched out using a press die. The clearance was set to 3.5% of the thickness of the test material. Of the four cuts (end faces) formed on the square test piece, two opposing cuts were punched out so as to be perpendicular to the rolling direction. Figure 2 schematically shows the shape of the cuts of the punched test piece. The size of the burrs, etc., are depicted in an exaggerated manner. For the cuts perpendicular to the rolling direction of the test piece, the surface height when the cut is viewed in the direction normal to the cut (in this case, a direction perpendicular to both the rolling direction and the thickness direction) was measured along the entire length in the thickness direction (punch axis direction) using a laser microscope, and a surface roughness profile was created. From this profile, the length of the shear surface indicated by symbol A in Figure 2 was determined, and the ratio of the shear surface to the fracture surface was calculated. Here, for the sake of ease of measurement, the length including the burr portion indicated by symbol B in Figure 1 was considered as the length of the fracture surface, and the "shear ratio" was calculated using the following formula (2). In this press punching test, the burr height is usually less than 1 μm, so including the burr in the length of the fracture surface does not hinder the evaluation of press punchability. Shear area ratio (%) = 100 × A / (A + B) …(2) This measurement was performed at 10 locations within the cross-section (end face) parallel to the rolling direction of the test specimen. The shear area ratio was calculated at each location using equation (2), and the arithmetic mean of these values was adopted as the shear area ratio of the test material. In this test, if the shear area ratio at a clearance of 3.5% is 34% or less (the shear area ratio at a clearance of 5% is 35% or less), it can be judged that a significant improvement in press punching performance is observed compared to conventional Colson-type copper alloy sheet materials. Therefore, specimens with a shear area ratio of 34% or less at a clearance of 3.5% (the shear area ratio at a clearance of 5% is 35% or less) were judged to be acceptable. It is more preferable that the shear area ratio at a clearance of 5% or 3.5% is 30% or less. Furthermore, in this test, under the condition of a clearance of 10%, if the shear area ratio is 17% or less, it can be judged that a significant improvement in press punching performance is observed compared to conventional Colson-type copper alloy sheet materials. Therefore, we determined that products with a shear surface ratio of 17% or less at a 10% clearance were acceptable.
[0054] (Volume fraction of {200} crystal planes) Using an X-ray diffractometer (BRUKER D2 PHASER 2ndGen) with a Cu tube, tube voltage of 30kV, and tube current of 10mA, the integrated intensities of the X-ray diffraction peaks I{111}, I{200}, I{220}, I{311}, I{331}, and I{420} planes in the X-ray diffraction pattern (profile) obtained for the plate surface (rolled surface) of the test specimen were analyzed. In addition to measuring I{331} and I{420}, the integrated intensities I0{111}, I0{200}, I0{220}, I0{311}, I0{331}, and I0{420} of the X-ray diffraction peaks in the {111}, {200}, {220}, {311}, {331}, and {420} planes of the X-ray diffraction pattern (profile) of pure copper standard powder were also measured. For the pure copper standard powder, commercially available copper powder with a purity of 99.5% and a mesh size of 325 (JIS Z8801) was used. Next, the integrated intensity of each diffraction peak on each crystal plane of the test specimen was divided by the integrated intensity of each diffraction peak on each crystal plane of the pure copper standard powder to obtain a correction intensity, and the sum of these correction intensities was defined as the "total correction intensity." Furthermore, the correction intensity I{200} / I0{200} was defined as the "correction intensity of the {200} crystal plane," and its ratio to the "total correction intensity" was defined as the "volume fraction (%) of the {200} crystal plane." The calculation formula is shown below. Total correction strength = I{111} / I0{111}+I{200} / I0{200}+I{220} / I0{220}+I{311} / I0{311}+I{331} / I0{331}+I{420} / I0{420} Volume fraction (%) of {200} crystal planes = Correction strength of {200} crystal planes / Total correction strengths × 100
[0055] The results are shown in Tables 1 to 5.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] [Table 4]
[0060] [Table 5]
[0061] In the test materials of the present invention (Examples 1-11) in which a predetermined amount of sulfur was contained and the structure was controlled, a remarkable improvement in press punchability was obtained in all cases while maintaining good bendability, and the tensile strength in the rolling direction was 700 MPa or higher, indicating a high strength level, and the conductivity was also good at 40% IACS or higher.
[0062] In contrast, in Comparative Example 31, the intermediate annealing temperature was outside the range specified by the present invention, resulting in a volume fraction of {200} crystal planes determined from the X-ray diffraction pattern of the obtained test material being less than 29%, and consequently, poor bendability. Comparative Examples 32 and 33 did not contain S and Mn, and the shear area ratio at a clearance of 3.5% exceeded 34%, resulting in poor press punching properties. Furthermore, Comparative Example 33 also did not have sufficient bendability.
[0063] Comparative Examples 34-36 were examples containing S and Mg, in which the first intermediate rolling and intermediate annealing processes were omitted, resulting in poor bendability.
[0064] Comparative Example 37 is an example in which intermediate annealing was omitted, and the volume fraction of {200} crystal planes determined from the X-ray diffraction pattern of the obtained test material was less than 29%, resulting in poor bendability. Comparative Example 38 is an example in which the sulfur content is high, no manganese is added, and the intermediate annealing temperature is outside the range specified in the present invention. As a result, the volume fraction of {200} crystal planes was less than 29%, and consequently, the bendability was poor. Comparative Example 39 is an example in which the amount of Mn is high, no S is added, and the intermediate annealing temperature is outside the range specified in the present invention. However, similar to Comparative Example 38, the volume fraction of {200} crystal planes was less than 29%, resulting in poor bendability. The shear area ratio at a clearance of 5% exceeded 35%, resulting in poor press punching performance. In addition, S tends to precipitate as particles, while Mn tends to dissolve in solid solution, so a decrease in conductivity was also observed in Comparative Example 39. Comparative Example 40 had poor conductivity due to its high S and Mn content. Furthermore, the intermediate annealing temperature was outside the range specified in the present invention, and the volume fraction of {200} crystal planes determined from the X-ray diffraction pattern of the obtained test material was less than 29%, resulting in poor bendability. Comparative Example 41 had insufficient strength due to its low Ni content. The intermediate annealing temperature was also outside the range specified in the present invention, and the volume fraction of {200} crystal planes determined from the X-ray diffraction pattern of the obtained test material was less than 29%. However, the bendability improved due to the low strength, and it was deemed acceptable. Comparative Example 42 was an example with an excessive amount of Ni, and cracking occurred during the hot rolling process, so the subsequent process was not carried out. Comparative Examples 43 and 44 had intermediate annealing temperatures outside the specified range of the present invention, and the volume fraction of {200} crystal planes determined from the X-ray diffraction patterns of the obtained test materials was less than 29%, resulting in poor bendability. Comparative Example 45 omitted the first intermediate rolling and intermediate annealing processes, resulting in a volume fraction of {200} crystal planes, determined from the X-ray diffraction pattern of the obtained test material, being less than 29%, and consequently exhibiting poor bendability.
Claims
1. In mass percent, Ni: 1.0-5.0%, Si: 0.2-1.5%, S: 0.001-0.5%, Mn: 0.001-0.5%, Co: 1.5% or less, It has a chemical composition consisting of the remainder being Cu and unavoidable impurities. The volume fraction of {200} crystal planes, determined from the X-ray diffraction pattern of the plate surface, is 29% or more. Copper alloy plate material.
2. The copper alloy plate material according to claim 1, wherein the (Ni + Co) / Si mass ratio is 3.0 to 6.
0.
3. The copper alloy plate material according to claim 1, wherein the Ni content is 1.0 to 4.5% by mass.
4. The copper alloy sheet material according to claim 1, wherein the tensile strength in the rolling direction is 700 MPa or more.
5. The copper alloy plate material according to claim 1, wherein the conductivity is 40% IACS or higher.
6. The copper alloy sheet material according to claim 1, wherein in a 90° L-shaped bending test at B.W., the ratio MBR / t of the minimum bending radius MBR at which no cracking occurs to the sheet thickness t is 1.0 or less.
7. The copper alloy sheet material according to claim 1, further comprising, in mass percent, Ag: 0-0.5%, Al: 0-0.5%, B: 0-0.1%, Cr: 0-0.5%, P: 0-0.5%, Sn: 0-0.5%, Ti: 0-0.5%, Zn: 0-0.5%, and Zr: 0-0.5%, with the total content of these being 0.001-1 mass percent.
8. An electrical component using a copper alloy plate material as described in any one of claims 1 to 7.
9. A heat dissipation component made using a copper alloy plate material as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Copper alloy sheet, method for production of copper alloy sheet, and electric / electronic component
JP2011231393A
Wrought copper alloy, copper alloy part, and process for producing wrought copper alloy
JP2011231394A
Copper alloy ingot and copper alloy material excellent in cutting workability, and copper alloy parts using the same
JP2012046812A
Cu-Ni-Si-BASED ALLOY AND METHOD FOR PRODUCING THE SAME
JP2012188689A
Copper alloy strip having improved dimensional accuracy after press working
JP2018159103A